Humanitarian Intervention between the Legal And Political Considerations: Humanitarian Intervention between the Legal And Political Considerations (Journal of the College of Education for Women, 2019)
Abstract:Humanitarian intervention has taken different forms included within thepeaceful and military means to stop the human suffering, whether caused bynatural disaster or humanitarian disasters.Intervention can not be acquitted because it carries with it political cover,but sometimes it may be legitimate cover for the occupation and the violationof sovereignty. Therefore, the research worked to capture the legal andpolitical aspects of international law and the role of international organizationsto intervene and the right to use force.The research concludes that international law had not been fairlysuccessful in controlling the behavior of some countries in the use of force,and that there is a gap between theory and actual practice of States in thisarea. Therefore, international law set several conditions that must be met bythis intervention to be legitimate. All that was included in this research.